EFFECT OF PHYNETOIN SODIUM ON LIVER FUNCTION TESTS - DR KASHINATH GUMMA; DR GAJANAN P KULKARNI (International Journal of Pharma and Bio Sciences, 2014)
Phenytoin sodium is the most commonly prescribed drug for the treatment of Grandmal epilepsy. The current study was conducted to evaluate the effect of Phenytoin sodium on liver function tests using serum AST, serum ALT, serum ALP as parameters. The results of the present study showed a significant increase in the levels of serum ALP in the epileptic patients on Phenytoin sodium as compared to control group. This increase in serum ALP could be a result of cholestasis induced by drug or as a consequence of hepatocellular toxicity.